2016
DOI: 10.1080/14756366.2016.1220377
|View full text |Cite
|
Sign up to set email alerts
|

NewN,N-dimethylcarbamate inhibitors of acetylcholinesterase: design synthesis and biological evaluation

Abstract: A series of N,N-dimethylcarbamates containing a N,N-dibenzylamino moiety was synthesized and tested to evaluate their ability to inhibit Acetylcholinesterase (AChE). The most active compounds 4 and 8, showed 85 and 69% of inhibition at 50 mM, respectively. Furthermore, some basic SAR rules were outlined: an alkyl linker of six methylene units is the best spacer between the carbamoyl and dibenzylamino moieties; electron-withdrawal substituents on aromatics rings of the dibenzylamino group reduce the inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Their anti-inflammatory effects [36], antimalarial activity [37], neuroprotective activities [38] have also been reported. They are also selective inhibitor of acetylcholinesterase (AChE) [39,40] with promising potential as therapeutic option for Alzheimer's disease treatment [41]. Our findings are consistent with the report of Shafika et al, [42]; they identified major polyphenols in avocado seeds to be catechin and pyrogallol, hesperidin, naringin and rutin.…”
Section: Acute Toxicity Studies On P Americana Seed Ethyl Acetate Fractionsupporting
confidence: 92%
“…Their anti-inflammatory effects [36], antimalarial activity [37], neuroprotective activities [38] have also been reported. They are also selective inhibitor of acetylcholinesterase (AChE) [39,40] with promising potential as therapeutic option for Alzheimer's disease treatment [41]. Our findings are consistent with the report of Shafika et al, [42]; they identified major polyphenols in avocado seeds to be catechin and pyrogallol, hesperidin, naringin and rutin.…”
Section: Acute Toxicity Studies On P Americana Seed Ethyl Acetate Fractionsupporting
confidence: 92%
“…A molecule is said to have more favorable binding modes with a better fit if the FF score shows greater negative value . The docked conformations having the lowest binding energy were selected for discussion . However, for the most favorable interaction, if a molecule has a small docking score, then it is said to have a higher binding affinity of ligands for a particular receptor .…”
Section: Resultsmentioning
confidence: 99%
“…44 The docked conformations having the lowest binding energy were selected for discussion. 45 However, for the most favorable interaction, if a molecule has a small docking score, then it is said to have a higher binding affinity of ligands for a particular receptor. 46 The FF score, binding affinity, and active residues of docked conformations are depicted in Table 7.…”
Section: Prediction Of Admet and Related Propertiesmentioning
confidence: 99%
“…The current treatment of AD is only symptomatic and mainly involves restoring of acetylcholine (ACh) levels through acetylcholinesterase (AChE) inhibition [ 71 ]. Three AChE inhibitors, namely donepezil, galanthamine ( 13 ) and rivastigmine, are currently used as the main therapeutic option for AD treatment [ 72 ]. Since the Amaryllidaceae alkaloid galanthamine ( 13 ) has been introduced into clinical practice, other Amaryllidaceae alkaloids have received attention as potential AChE inhibitors [ 5 , 73 , 74 , 75 , 76 ].…”
Section: Studied Biological Activities Of Extracts and Alkaloids Imentioning
confidence: 99%